Thinking about free will - Inwagen, Peter Van (Cambridge : Cambridge University Press, 2017)
Peter van Inwagen, the author of the seminal book An Essay on Free Will (1983), has spent over forty years as a leading figure in the philosophical discussion surrounding the problem of free will. This volume compiles eleven influential essays from various stages of his career, along with two new, previously unpublished essays, The Problem of Free Will and Ability. The essays cover topics such as determinism, moral responsibility, Frankfurt counterexamples, the concept of "the ability to do otherwise," and the very definition of free will, along with critiques of works by Daniel Dennett and David Lewis. An introduction by van Inwagen himself traces the evolution of his thoughts on free will. This collection will serve as a valuable resource for anyone looking to engage with van Inwagen's important contributions to this enduring philosophical issue.
1. Ability and responsibility; 2. On two arguments for compatibilism; 3. Compatibilistic reflections; 4. Critical study of Dennett's Elbow Room; 5. When is the will free?; 6. Moral responsibility, determinism, and the ability to do otherwise; 7. Free will remains a mystery; 8. Genes, statistics, and desert; 9. Freedom to break the laws; 10. How to think about the problem of free will; 11. A promising argument; 12. Preface to the French translation of An Essay on Free Will; 13. The problem of fr** w*ll; 14. Ability
Includes index.
Keywords: Philosophy; Free will and determinism